Drosophila Model of Human Inherited Triosephosphate Isomerase Deficiency Glycolytic Enzymopathy - Celotto, Alicia M. (Copyright © 2006 by the Genetics Society of America, 2006)
Heritable mutations, known as inborn errors of metabolism, cause numerous devastating human diseases, typically as a result of a deficiency in essential metabolic products or the accumulation of toxic intermediates. We have isolated a missense mutation in the Drosophila sugarkill (sgk) gene that causes phenotypes analogous to symptoms of triosephosphate isomerase (TPI) deficiency, a human familial disease, characterized by anaerobic metabolic dysfunction resulting from pathological missense mutations affecting the encoded TPI protein. In Drosophila, the sgk gene encodes the glycolytic enzyme TPI. Our analysis of sgk mutants revealed TPI impairment associated with reduced longevity, progressive locomotor deficiency, and neural degeneration. Biochemical studies demonstrate that mutation of this glycolytic enzyme gene does not result in a bioenergetic deficit, suggesting an alternate cause of enzymopathy associated with TPI impairment.